Hubungan antara depresi, kecemasan dan stress dengan motivasi berprestasi atlet putri selama pandemi covid 19 - Dita Yuliastrid; Suryanto Suryanto; Anung Priambodo (Journal Of Sport Education (JOPE), 2021)
The Covid-19 pandemic can certainly affect the performance and psychological condition of athletes. The purpose of this study was to describe the relationship between depression, anxiety and stress on achievement motivation in female athletes during the pandemic. This study uses a quantitative approach research method. The sample used was female athletes, amounting to 65 people. Data collection techniques using online questionnaires via google form. The questionnaire used in this study was the Depression Anxiety Stress Scale 42 (DASS 42) from Lovibond and Lovibond (1995) and the achievement motivation questionnaire. Data analysis was carried out using the Kendal tau correlation technique with the help of the SPSS 21 program. The results showed a negative correlation between depression and motivation of (-0.65); a significance value of 0.000 (p<0.05), between anxiety and motivation of (-0.57); a significance value of 0.000 (p<0.05), between stress and motivation of (-0.51); significance value 0.000 (p<0.05). The conclusion is that the higher the level of depression, anxiety and stress, the lower the athlete's achievement motivation, the relationship between depression and achievement motivation is in the strong category, anxiety and achievement motivation is in the medium category, and between stress and achievement motivation is in the medium categoryCopyright © The Author (s) 2021Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.